2011
DOI: 10.1002/cbdv.201000254
|View full text |Cite
|
Sign up to set email alerts
|

Components of Essential Oils Extracted from Leaves and Shoots of Abies Species in Japan

Abstract: The essential oils extracted from the leaves and the shoots of five Abies species (Pinaceae) growing in Japan, i.e., A. firma, A. homolepis, A. veitchii, A. mariesii, and A. sachalinensis, were characterized by GC-FID and GC/MS analyses. The yields of the essential oils extracted from A. sachalinensis were the highest among them. A significant amount of α-pinene was contained in the essential oils of all the Abies species examined. In A. homolepis and A. veitchii, significant differences in the content of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 11 publications
0
7
0
Order By: Relevance
“…24 On the other hand, (+)-camphene was the major enantiomer in A. spectabilis , 25 A. procera , 28 and Russian A. sibirica (Table 3) essential oils. The only enantiomer of δ-3-carene in A. concolor foliar essential oil was (+)-δ-3-carene, consistent with that observed for A. firma , A. mariesii , 24 A. spectabilis subsp. langtangensis , 25 A. procera , 28 A. balsamea and A. sibirica (Table 3) essential oils.…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…24 On the other hand, (+)-camphene was the major enantiomer in A. spectabilis , 25 A. procera , 28 and Russian A. sibirica (Table 3) essential oils. The only enantiomer of δ-3-carene in A. concolor foliar essential oil was (+)-δ-3-carene, consistent with that observed for A. firma , A. mariesii , 24 A. spectabilis subsp. langtangensis , 25 A. procera , 28 A. balsamea and A. sibirica (Table 3) essential oils.…”
Section: Resultsmentioning
confidence: 98%
“…On the other hand, ( + )-α-pinene was the dominant enantiomer in the leaf essential oil of A. sibirica from Austria, 22 A. sibirica from Russia (Table 3), Abies firma Siebold & Zucc. leaf essential oil from Japan, 24 and the leaf essential oil of Abies spectabilis subsp. langtangensis (Silba) Silba from Nepal.…”
Section: Resultsmentioning
confidence: 99%
“…In previous studies, Satou et al 14 reported that the essential oils of Abies firma contained bornyl acetate, δ-cadinene, camphene, δ-3-carene, βcaryophyllene, α-humulene, isoledene, limonene, longifolene, α-muurolene, myrcene, α-pinene, and terpinolene. In contrast with this study, Chaudhary 15 showed that the major components of Cedrus deodara oil were αcedrene, α-himachalene, β-himachalene, and γhimachalene.…”
Section: Resultsmentioning
confidence: 99%
“…Multiple studies have been dedicated to investigating the chemical compositions and antibacterial and antifungal activities of essential oils extracted from Abies plants ( Lee and Hong, 2009;Satou et al, 2011). Various bioactive compounds such as lignans and triterpenoids have been isolated from several Abies species (Roshchin et al, 1998;Kim et al, 1999).…”
Section: Figurementioning
confidence: 99%
“…The essential oils extracted from the leaves and the shoots of five Abies species (Pinaceae) growing in Japan, i.e., A. firma, A. homolepis, A. veitchii, A. mariesii, and A. sachalinensis, were characterized by GC-FID and GC/MS analyses (Satou et al, 2011).…”
Section: Figurementioning
confidence: 99%